2011
DOI: 10.1002/anie.201007327
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Aspergillide A and B Based on the Transannular Oxy‐Michael Reaction

Abstract: The aspergillides A, B, and C (1, 2, and 3) comprise a novel class of 14-membered macrolides that were isolated by Kusumi and co-workers from the marine-derived fungus Aspergillus ostianus strain 01F313 that was cultured in a medium composed of bromine-modified artificial sea water. [1] Their structures were determined by extensive spectroscopic studies, and their absolute configurations were established by X-ray crystallography (for 1 and 2) and the modified Mosher method (for 3).[2] These compounds contain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…To date, three total syntheses, 2 one of which is a formal synthesis, 2b have been reported. Herein we describe the secondgeneration total synthesis of the natural enantiomer (+)-aspergillide C (1) from the bicyclic acetal 5 that was prepared from 6 3 via a 4-step sequence and used for the syntheses of aspergillides A and B, 4 the key step of which employs an interesting 6-exo-trig transannular oxy-Michael reaction providing the tetrahydropyran moiety. 5 Since such a process has not yet been reported, the pivotal transannular cyclization of 2 to afford the dihydropyran incorporated in the macrolide 1 could prove to be challenging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three total syntheses, 2 one of which is a formal synthesis, 2b have been reported. Herein we describe the secondgeneration total synthesis of the natural enantiomer (+)-aspergillide C (1) from the bicyclic acetal 5 that was prepared from 6 3 via a 4-step sequence and used for the syntheses of aspergillides A and B, 4 the key step of which employs an interesting 6-exo-trig transannular oxy-Michael reaction providing the tetrahydropyran moiety. 5 Since such a process has not yet been reported, the pivotal transannular cyclization of 2 to afford the dihydropyran incorporated in the macrolide 1 could prove to be challenging.…”
mentioning
confidence: 99%
“…In summary, the second-generation enantioselective total synthesis of aspergillide C (1) has been accomplished in a longest linear sequence of 15 steps from the bicyclic chiral building block 6 in 19% overall yield. It was revealed that the 6-exo-trig transannular oxy-Michael reaction of the macrolide 2 with the non-protected Z-allylic diol and the enoate functionalities proceeded smoothly to produce the substituted dihydropyran-containing macrolide, namely aspergillide C (1), in a shorter period of time compared to the corresponding dihydro-substrate, 4 which was used previously for the synthesis of aspergillides A and B. We also completed the first, efficient enantioselective synthesis of 3-epi-aspergillide C (15) from the common substrate 2, and demonstrated the successful conversion of 15 to aspergillide C (1).…”
mentioning
confidence: 99%
“…A stock solution of 0.1 M DBU in C 6 D 6 was prepared and used as the reaction solvent for both diastereomers 21 and 14 . Contrary to the successful use of DBU in the oxa-conjugate additions observed for both linear and transannular systems by Fuwa and Shishido, , respectively, 21 and 14 were unreactive at room temperature and completely consumed at reflux without observable formation of the desired THP product. Elimination, leading toward formation of sorbate containing compounds, predominated.…”
Section: Resultsmentioning
confidence: 58%
“…To access the trans -disubstituted tetrahydropyran skeleton, we considered base-promoted cyclization according to a stereoselectivity model proposed by Shishido. 13 After investigating a number of bases and reaction conditions, it was found that a one-pot sequential CM/oxa-Michael addition process in the presence of 1,8-diazabicyclo-[5,4,0]-undec-7-ene (DBU) at ambient temperature initiated a rapid and clean intramolecular cyclization of intermediate 12 to give trans -3,7-disubstituted tetrahydropyran 16 in 63% yield, along with the cis -disubstituted tetrahydropyran lactone 17 (16%) as a side product. One-pot tandem acetonide deprotection and lactonization of 16 was accomplished with 50% TFA and afforded the desired bicyclic dioxabicyclo[3.3.1]nonane lactone 6 in a good yield of 79%.…”
Section: Resultsmentioning
confidence: 99%